2004
DOI: 10.1023/b:nere.0000014823.74782.b7
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Function in Apoptotic Neuronal Cell Death

Abstract: Apoptosis can be defined as the regulated death of a cell and is conducted by conserved pathways. Apoptosis of neurons after injury or disease differs from programed cell death, in the sense that neurons in an adult brain are not "meant" to die and results in a loss of function. Thus apoptosis is an honorable process by a neuron, a cell with limited potential to replace itself, choosing instead to commit suicide to save neighboring cells from release of cellular components that cause injury directly or trigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 114 publications
1
32
1
Order By: Relevance
“…Consistent with the loss of complex V, we found that mitochondrial ATP was also decreased during hypoxia. Mitochondria provide almost all the ATP necessary for normal neuronal functions and ATP has been identified as one of the key factors determining cellular apoptosis or necrosis: maintenance of ATP production is associated with apoptosis, whereas a rapid decline of mitochondrial function and ATP is associated with necrosis (20). In our case, normal ATP production was not restored after incubation of synaptosomes in 2% O 2 and in anoxia.…”
Section: Discussioncontrasting
confidence: 51%
“…Consistent with the loss of complex V, we found that mitochondrial ATP was also decreased during hypoxia. Mitochondria provide almost all the ATP necessary for normal neuronal functions and ATP has been identified as one of the key factors determining cellular apoptosis or necrosis: maintenance of ATP production is associated with apoptosis, whereas a rapid decline of mitochondrial function and ATP is associated with necrosis (20). In our case, normal ATP production was not restored after incubation of synaptosomes in 2% O 2 and in anoxia.…”
Section: Discussioncontrasting
confidence: 51%
“…The mitochondrion has been shown to be a key participant in TBI-induced neuropathology, 16 and its dysfunction has serious implications for outcome following head injury. Indeed, compared with patients with marginal mitochondrial impairment, who demonstrate a good outcome, TBI patients with profound mitochondrial impairment have a poor prognosis.…”
Section: Mitochondriamentioning
confidence: 99%
“…Ischemia-induced decrease in MPT is coupled with the release of cytochrome c from mitochondria to cytoplasm (Budd-Haeberlein, 2004). In this study, the hippocampal CA1 region was dissected at 48 hr after I/R and homogenized in buffer (20 mM HEPES, pH 7.5, 0.25 M sucrose, 10 mM KCl, 1.5 mM MgCl 2 , 1 mM EDTA, 1 mM EGTA, and 1 mM dithiothreitol) together with a protease inhibitor cocktail.…”
Section: Measurement Of Cytochrome C Releasementioning
confidence: 99%
“…V Cessation of blood flow and lack of oxygen supply in cerebral ischemia are known to cause neuronal excitation together with release of excitatory neurotransmitters (Ikemune et al, 1999). In turn, this can trigger a series of cellular events, including synaptic membrane depolarization, influx of calcium, increase in production of reactive oxygen species (ROS), mitochondrial dysfunction, and finally neuronal apoptosis (Nitatori et al, 1995;Nakamura et al, 1999;Hara et al, 2000;Kirino, 2000;Won et al, 2001;Budd-Haeberlein, 2004). Increase in ROS is known to cause oxidative damage to lipids, proteins, and DNA (Sun and Chen, 1998;Love, 1999;Lewen et al, 2000;Chan, 2001) and has been an important underlying factor in ischemia/reperfusion (I/R)-induced delayed neuronal death (DND; Kirino, 2000).…”
mentioning
confidence: 99%